AN ANTHROPOLOGICAL PERSPECTIVE ON THE GASTRONOMY OF THE MARAMS IN MANIPUR (International Journal of Food and Nutritional Sciences, 2022)
Food is not only essential for human nutrition. Rather, the food habit of a society satisfies hunger, provides comfort, express cohesion and reflects the social identity. The present study describes the food in socio-cultural canvas of the Maram who belong to the particularly vulnerable tribe of Manipur in the northeastern corner of India. Just as many anthropologists and social scientists view the food habit to be shaped by culture, the people in context have positive and negative food regardless of dietary food value. Though majority of the tribal peoples in the state are fond of pork, the Marams avoid it. In addition, they have their own gastronomy to relish community feast and festival.